New Clox Systems for rapid and efficient gene disruption in Candida albicans. - Shahida Shahana; Delma S Childers; Elizabeth R Ballou; Iryna Bohovych; Frank C Odds; Neil A R Gow; Alistair J P Brown (PLoS ONE, 2014)
Precise genome modification is essential for the molecular dissection of Candida albicans, and is yielding invaluable information about the roles of specific gene functions in this major fungal pathogen of humans. C. albicans is naturally diploid, unable to undergo meiosis, and utilizes a non-canonical genetic code. Hence, specialized tools have had to be developed for gene disruption in C. albicans that permit the deletion of both target alleles, and in some cases, the recycling of the Candida-specific selectable markers. Previously, we developed a tool based on the Cre recombinase, which recycles markers in C. albicans with 90-100% efficiency via site-specific recombination between loxP sites. Ironically, the utility of this system was hampered by the extreme efficiency of Cre, which prevented the construction in Escherichia coli of stable disruption cassettes carrying a methionine-regulatable CaMET3p-cre gene flanked by loxP sites. Therefore, we have significantly enhanced this system by engineering new Clox cassettes that carry a synthetic, intron-containing cre gene. The Clox kit facilitates efficient transformation and marker recycling, thereby simplifying and accelerating the process of gene disruption in C. albicans. Indeed, homozygous mutants can be generated and their markers resolved within two weeks. The Clox kit facilitates strategies involving single marker recycling or multi-marker gene disruption. Furthermore, it includes the dominant NAT1 marker, as well as URA3, HIS1 and ARG4 cassettes, thereby permitting the manipulation of clinical isolates as well as genetically marked strains of C. albicans. The accelerated gene disruption strategies afforded by this new Clox system are likely to have a profound impact on the speed with which C. albicans pathobiology can be dissected.